GLONASS-K attitude: rapid turning maneuvers and other deviations from ideal yaw steering - Florian Dilssner; Tim Springer (GPS Solutions, 2024)

Combination strategy for consistent final, rapid and predicted Earth rotation parameters - Alexander Kehm; Hendrik Hellmers; Mathis Bloßfeld; Robert Dill; Detlef Angermann; Florian Seitz; Urs Hugentobler; Henryk Dobslaw; Maik Thomas; Daniela Thaller; Johannes Böhm; Erik Schönemann; et al. (Journal of Geodesy, 2023)
The accurate knowledge of the Earth’s orientation and rotation in space is essential for a broad variety of scientific and societal applications. Among others, these include global positioning, near-Earth and deep-space navigation, the realisation of precise reference and time systems as well as studies of geodynamics and global change phenomena. In this paper, we present a refined strategy for processing and combining Very Long Baseline Interferometry (VLBI), Satellite Laser Ranging (SLR), Global Navigation Satellite Systems (GNSS), and Doppler Orbitography and Radiopositioning Integrated by Satellite (DORIS) observations at the normal equation level and formulate recommendations for a consistent processing of the space-geodetic input data. Based on the developed strategy, we determine final and rapid Earth rotation parameter (ERP) solutions with low latency that also serve as the basis for a subsequent prediction of ERPs involving effective angular momentum data. Realising final ERPs on an accuracy level comparable to the final ERP benchmark solutions IERS 14C04 and JPL COMB2018, our strategy allows to enhance the consistency between final, rapid and predicted ERPs in terms of RMS differences by up to 50% compared to existing solutions. The findings of the study thus support the ambitious goals of the Global Geodetic Observing System (GGOS) in providing highly accurate and consistent time series of geodetic parameters for science and applications.

Effect of Nitrogen Fertilization on Biomass Yield of Sand Bluestem (Andropogon hallii Hack.) - Tim L. Springer (BioEnergy Research, 2021)

On the interoperability of IGS products for precise point positioning with ambiguity resolution - Simon Banville; Jianghui Geng; Sylvain Loyer; Stefan Schaer; Tim Springer; Sebastian Strasser (Journal of Geodesy, 2020)

Recurrent selection increases seed germination in little bluestem (Schizachyrium scoparium) - Tim L. Springer (Euphytica, 2017)

Effect of Nitrogen Fertilization and Residual Nitrogen on Biomass Yield of Switchgrass - Tim L. Springer (BioEnergy Research, 2017)

A collinearity diagnosis of the GNSS geocenter determination - Paul Rebischung; Zuheir Altamimi; Tim Springer (Journal of Geodesy, 2014)

Estimation of phase center corrections for GLONASS-M satellite antennas - Florian Dilssner; Tim Springer; Claudia Flohrer; John Dow (Journal of Geodesy, 2010)

IGS Near Real-Time Products and Their Applications - Peng Fang; Gerd Gendt; Tim Springer; Tony Mannucci (GPS Solutions, 2001)

Progress in Carrier Phase Time Transfer - Jim Ray; Felicitas Arias; Gérard Petit; Tim Springer; Thomas Schildknecht; Jon Clarke; Jan Johansson (GPS Solutions, 2001)

New IGS Station and Satellite Clock Combination - Jan Kouba; Tim Springer (GPS Solutions, 2001)

A Discussion of IGS Solutions and Their Impact on Geodetic and Geophysical Applications - Jan Kouba; Yves Mireault; Gerhard Beutler; Tim Springer; Gerd Gendt (GPS Solutions, 1998)